2020
DOI: 10.1007/s10096-020-03860-5
|View full text |Cite
|
Sign up to set email alerts
|

Performance and ease of use of a molecular point-of-care test for influenza A/B and RSV in patients presenting to primary care

Abstract: Annual influenza epidemics cause substantial morbidity and mortality, and the majority of patients with influenza-like illness present to primary care. Point-of-care influenza tests could support treatment decisions. It is critical to establish analytic performance of these platforms in real-life patient samples before uptake can be considered. We aimed to assess the analytical performance and ease of use of the cobas® Liat® PCR POCT in detecting influenza A/B and RSV in samples collected from patients with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Liat SARS-CoV-2 Manuscript JCM submission 19NOV2020 performance for influenza A/B detection as well as overall assay workflow and field usability were established in previous studies (10)(11)(12) (10,11,13,14).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Liat SARS-CoV-2 Manuscript JCM submission 19NOV2020 performance for influenza A/B detection as well as overall assay workflow and field usability were established in previous studies (10)(11)(12) (10,11,13,14).…”
Section: Downloaded Frommentioning
confidence: 99%
“…20,21 Since the sensitivity (98.8%) and specificity (98.5%) of POC PCR using Liat is very high and invalid results are rare, a reliable result that influenced the adoption of isolation measures and initiation of therapy was available very quickly. [16][17][18][19] PERLITZ ET aL.…”
Section: Discussionmentioning
confidence: 99%
“…According to current studies, a POC test performing a RT-PCR is a promising method with high sensitivity and specificity to enable a faster availability of test results directly in the ED. [16][17][18][19] Previous studies mainly focused on TAT and have shown strong effects on the length of stay (LOS). [20][21][22][23] The effects on frequency of antibiotic or antiviral therapy with NAI varied from study to study.…”
Section: Introductionmentioning
confidence: 99%
“…Before routine application, the laboratory should conduct independent performance verification of the POCT system to verify that its performance is consistent with declared performance indicators ( International Organization for Standardization, 2012a ; International Organization for Standardization. 2015 ; International Organization for Standardization, 2016 ; International Organization for Standardization, 2020; Verbakel et al, 2020 ). If any situation that seriously affects the analytical performance of the testing programme occurs, for example, when the main components (such as the fluorescence channel) have been repaired or replaced, performance should be verified before the testing programme is reactivated ( International Organization for Standardization, 2012a ; International Organization for Standardization, 2016 ).…”
Section: Performance Verification Of Testing Programmesmentioning
confidence: 99%